Ḍahīrah Ḥarakah Taṭbīq al-Sharī’ah al-Islāmīyah bi Cianjur: Dirāsah Tamhīdīyah - Tasman Tasman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2005)
This piece focuses its attention on the process of 'the implementation of Islamic law in Cianjur' in West Java, in the local social-political context. The background to the ideology and concept of the implementation of Islamic law in Cianjur is a response to social and political developments both locally and nationally. Cianjur is a region which encourages and supports Gerakan Pembangunan Masyarakat Beraklakul Karimah (The Movement for the Development of a Society with Good Character) - often referred to as Gerbang Marhamah.DOI: 10.15408/sdi.v12i2.591